State Housing Fund and Municipal Services Measures (Eurasian Research Bulletin, 2022)
This article discusses measures to establish the state housing fund and utilities. The author clarifies the problem on the basis of available data, based on economic data and scientific sources. It provides a comparative analysis of existing approaches and theories on public housing and utilities